Interpersonal dysfunction and treatment outcome in GAD: A systematic review. (December 2020) - Malivoire, Bailee L.; Mutschler, Christina; Monson, Candice M.
Highlights: We review the relationship between interpersonal dysfunction and treatment for GAD. Interpersonal dysfunction generally improves in treatment for GAD. However, greater interpersonal dysfunction predicts worse outcomes. Some maladaptive interpersonal behaviors do not reliably improve following treatment. Some patients would benefit from focused interventions for interpersonal dysfunction. Abstract: Interpersonal dysfunction is posited to maintain worry and generalized anxiety disorder (GAD). It has been suggested that the low remission rates in psychotherapy for GAD may be attributable, in part, to inadequately addressing interpersonal dysfunction. This paper systematically reviewed the literature examining the moderating role of interpersonal dysfunction on GAD psychotherapy outcomes and change in interpersonal dysfunction over the course of GAD treatment. Thirteen studies were identified, seven of which examined the relationship between interpersonal dysfunction or distress and treatment outcome and nine investigated change in interpersonal dysfunction over the course of psychotherapy. The majority of studies indicated that interpersonal dysfunction improves following psychotherapy. However, there is preliminary evidence that not all subscales of interpersonal dysfunction improve, including subscales relevant to GAD pathology such as overly-nurturant dysfunction. Further, greater interpersonal dysfunction predicted worse treatment outcomes. As such, interpersonal dysfunction may hinder treatment success and further research is needed to delineate for whom additional or integrated interpersonal interventions may be needed. Approaches to target interpersonal dysfunction in GAD are discussed.